Genetic and transcriptomic analysis of lentil seed imbibition and dormancy in relation to its domestication - Azalea Guerra‐García; Jana Balarynová; Petr Smykal; Eric J vonWettberg; Scott D. Noble; Kirstin E. Bett (The Plant Genome)
Abstract Seed dormancy is an adaptation that delays germination to prevent the start of this process during unsuitable conditions. It is crucial in wild species but its loss was selected during crop domestication to ensure a fast and uniform germination. Water uptake, or imbibition, is the first step of germination. In the Fabaceae family, seeds have physical dormancy, in which seed coats are impermeable to water. We used an interspecific cross between an elite lentil line (Lens culinaris) and a wild lentil (L. orientalis) to investigate the genetic basis of imbibition capacity through quantitative trait locus (QTL) mapping and by using RNA from embryos and seed coats at different development stages, and phenotypic data of seed coat thickness (SCT) and proportion of imbibed seeds (PIS). Both characteristics were consistent throughout different years and locations, suggesting a hereditary component. QTL results suggest that they are each controlled by relatively few loci. Differentially expressed genes (DEGs) within the QTL were considered candidate genes. Two glycosyl‐hydrolase genes (a β‐glucosidase and a β‐galactosidase), which degrade complex polysaccharides in the cell wall, were found among the candidate genes, and one of them had a positive correlation (β‐glucosidase) between gene expression and imbibition capacity, and the other gene (β‐galactosidase) presented a negative correlation between gene expression and SCT.